Rethinking language policy and planning in the Greater Bay Area of China: insights from translanguaging theory - Zhisheng (Edward) Wen; Lili Han; Guangwei Hu; Mark Feng Teng (Asian-Pacific Journal of Second and Foreign Language Education, 2022)
Abstract This special issue sets out to revisit major bilingual and multilingual education policy and planning issues in key cities across the dynamic Greater Bay Area (GBA) of China (including Guangdong, Hong Kong, and Macau), as informed by the emerging insights from translanguaging theory (Li in Appl Linguist 39(1):9–30, 2018). Specifically, contributions are invited from the GBA and beyond to trace the milestone developments of relevant language policy and planning (LPP) initiatives featuring governmental policies on the language of instruction (e.g., English as Medium of Instruction, Chinese as Medium of Instruction) and the daily use of multiple linguistic resources or repertoires (e.g., language learner's L1 or mother tongue) in foreign/second language classrooms and/or in content-based classroom instruction. As such, major papers in the special issue not only set out to provide historical and analytical reviews of these related LPP issues across Hong Kong, Macau, and Guangdong Province but also reflect upon the language use and behaviors of the residents, showcasing their identity and attitudes and ideological stance toward the multiple languages that are being taught or used in daily life. Toward the end, we outline our research agendas for future endeavors in broader domains in the GBA and beyond through the translanguaging analytical tools. Overall, our position is that the GBA presents itself as an evolving, complex, and superdiverse zone of “Translanguaging Spaces” within which key LPP issues may need to be reconceptualized and implemented in such a way so as to fully reflect the dynamic and fluid multilingual, multicultural, and multisemiotic lived reality of the residents in this megapolis region.